2016
DOI: 10.3390/nu8110693
|View full text |Cite
|
Sign up to set email alerts
|

The Proportion of Anemia Associated with Iron Deficiency in Low, Medium, and High Human Development Index Countries: A Systematic Analysis of National Surveys

Abstract: Iron deficiency is commonly assumed to cause half of all cases of anemias, with hereditary blood disorders and infections such as hookworm and malaria being the other major causes. In countries ranked as low, medium, and high by the Human Development Index, we conducted a systematic review of nationally representative surveys that reported the prevalence of iron deficiency, iron deficiency anemia, and anemia among pre-school children and non-pregnant women of reproductive age. Using random effects meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
331
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(356 citation statements)
references
References 28 publications
17
331
1
7
Order By: Relevance
“…In detail, results from studies conducted in the United States reported the prevalence of iron deficiency ranges from 4.5 to 18.0%. But the proportion of anaemia caused by iron deficiency in central Asia, south Asia and Andean Latin America were 64.7, 54.8 and 62.3%, respectively [8,40].…”
Section: Disease Burdenmentioning
confidence: 95%
“…In detail, results from studies conducted in the United States reported the prevalence of iron deficiency ranges from 4.5 to 18.0%. But the proportion of anaemia caused by iron deficiency in central Asia, south Asia and Andean Latin America were 64.7, 54.8 and 62.3%, respectively [8,40].…”
Section: Disease Burdenmentioning
confidence: 95%
“…Before the point when screening identifies IDA, the critical development of the brain, heart, and other tissues may already have been permanently impaired by ID in those tissues (12,20). Further, the recent report by Petry et al (24) suggests that only w25% of anemia is attributable to ID. Therefore, improvements in screening will depend in part on improving indicators that are particularly informative of tissue ID.…”
Section: Improving Assessment Of Iron Status In Pregnancy and Young Cmentioning
confidence: 99%
“…A ingestão de micronutrientes pelas crianças tem se mostrado inadequada, sobretudo em relação ao ferro, no cenário internacional (5)(6)(7)(8) e nacional (2,4) . Este nutriente é considerado como marcador de uma dieta de baixa qualidade e de práticas alimentares incorretas (2,4) .…”
unclassified
“…A anemia ferropriva, patologia resultante da carência de ferro, tem atingido muitos lactentes (1,(5)(6)(7)10,11) . Nessa fase, a anemia está comumente relacionada com a interrupção precoce do aleitamento materno e a alimentação complementar oferecida de forma inadequada (3,10,12) .…”
unclassified